Leg dominances effect on balance in elite soccer players - Fletcher, I.; Long, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Soccer has a high prevalence of lower limb injuries (Gstottner et al., 2009); with non-contact ACL injuries more prevalent within the preferred rather than non-preferred kicking leg (Brophy, 2010). This could suggest that leg asymmetry could be an inherent injury risk factor. Importantly, balance asymmetry has yet to be tested in the elite population. Therefore, this study aimed to compare kicking leg dominances effect on balance in elite players. Methods: 15 male elite soccer players (age 24 ±7 yr, height 183.86 ±5.16 cm, mass 79.9 ±9.13 kg) drawn from an English League One soccer team were assessed for balance asymmetry using an RSscan pressure plate (RSscan Ltd, Ipswich, United Kingdom). 1 legged static, dynamic (a one metre hop and hold) and passing action balance tests were assessed by measuring the deviation from the centre of pressure (CoP) in millimetres. Results: When the balance tests were compared a main effect was found (F=63.721, p<0.01, effect size=0.907), indicating that the static test was 10.5% (p=0.037) worse than the dynamic balance task. Leg dominance across all the balance tests was not linked to significant differences in CoP deviation (F=0.476, p=0.501, effect size=0.033). However, when pairwise comparisons were employed, though the static and dynamic balance tests showed leg symmetry (p>0.05), the pass test indicated that the dominant leg exhibited significantly worse dynamic balance than the non-dominant leg (33.3%, p=0.05). Discussion: This study`s results indicate that static balance was significantly better than dynamic test results. This could be important in terms of screening players for injury risk factors. Njorai (2010) states that players are always in motion, therefore balance systems are rarely required to maintain a stable base for more than a few moments. If this is the case than it brings into question the efficacy of static balance tests. Interestingly, Lembert et al., (2006) has shown functional discrepancies between dominant and non-dominant legs. The present results on standard static and dynamic balance tasks do not support this supposition; however the specific kicking task test found a decreae in stability within the dominant kicking leg. It may be that in a highly trained soccer population leg inequalities are more apparent in specific balance tasks; this may mean that balance screening does not just have to be dynamic; it also has to incorporate a specific football task to explore leg discrepancies within players.